Políticas curriculares em Angola (2001 - 2015): o público e o privado - Bumba, António Maria (2017)
This dissertation aims to investigate, analyze and unveil political, ideological, social and educational assumptions that support the curriculum policy of the educational system in Angola. There is a growing and promising advance in the study of educational policies. However, the study of curricular policies, an essential object of educational policy, which governs and regulates the curricular minimums of education, establishing the rules of the game in the curricular system, remains scarce, practically nonexistent. Considering the state of the object, the problem and the objectives of the research, an exploratory approach methodological, of qualitative approach methodology was adopted. In combination with this approach, a bibliographical and documentary research was carried out, making use of and analysis of bibliographies and official documents produced by the special institutions of the Angolan State and others. As we felt the need to deepen the information about the object, we used the interview, as a subsidiary technique of data collection, with the technicians and managers of the Ministry of Education of Angola. Thus, it was possible to construct a productive dialogue with theoretical references used. In view of the (ongoing) state restructuring process, the change of political and economic system, that is, the transition from the Angolan State from the socialist to capitalist, single party (MPLA) system to a multiparty democracy, and a Socialist economy for the market economy - changes that inexorably require the reconfiguration of educational policies -, the new context leads us to reflect on a fundamental question, guiding the research: what assumptions guide and justify the general education curriculum policy in Angola? The results of the research show, therefore, that the assumptions that guide curriculum policy aim above all at the alignment of education and the educational curriculum with the market demand and the development of the capitalist system